2013
DOI: 10.1080/13573322.2011.609165
|View full text |Cite
|
Sign up to set email alerts
|

From PE experiences to PE teaching practices? Insights from Scottish primary teachers' experiences of PE, teacher education, school entry and professional development

Abstract: suggest that further research is needed to explore how non-specialist primary teachers approach and teach physical education (PE) based on their personal school PE backgrounds, teacher education experiences and ongoing professional development. This paper adopts Lawson's socialisation model, a theoretical framework subsequently used by many other researchers, to explore how primary teachers' experiences in various contexts 'shape [their] knowledge and beliefs about the purpose of physical education, its cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…The perceived shortcomings of generalist class teachers in this study adds weight to a wellrehearsed view (see, for example, Elliott, Atencio, Campbell, & Jess, 2013;Harris, Cale, & Musson, 2012;Morgan & Hansen, 2008) neatly summarized by Tsangaridou (2012, p. 281) thus: "A significant number of primary school teachers have low levels of confidence, do not possess the skills and knowledge to deliver appropriate PE instruction, have limited content knowledge and do not feel competent teaching PE". All-in-all, then, the main argument for sports coaches tended to be an implicitly negative one: put starkly, sports coaches were deemed better than many primary teachers because of the inherent weaknesses among the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived shortcomings of generalist class teachers in this study adds weight to a wellrehearsed view (see, for example, Elliott, Atencio, Campbell, & Jess, 2013;Harris, Cale, & Musson, 2012;Morgan & Hansen, 2008) neatly summarized by Tsangaridou (2012, p. 281) thus: "A significant number of primary school teachers have low levels of confidence, do not possess the skills and knowledge to deliver appropriate PE instruction, have limited content knowledge and do not feel competent teaching PE". All-in-all, then, the main argument for sports coaches tended to be an implicitly negative one: put starkly, sports coaches were deemed better than many primary teachers because of the inherent weaknesses among the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of PE as 'a core activity linked to healthy lifestyles, lifelong learning, improved health, an inclusive society' (Scottish Executive, 2004a, p. 2) has been emphasised in the new curriculum by requiring two hours or two periods per week of PE for every pupil in Scotland between 5 and 16 years of age (p. 10). These recent policy and curricular developments bring into focus the significance of professional growth and teacher development in general, particularly in primary PE where it was found that teachers lack the knowledge, skills and confidence to teach PE due to the limited subject input in primary ITE (Blair & Capel, 2011;Elliot et al, 2011;Morgan & Bourke, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tsangaridou (2012) concluded that many primary school teachers have limited CK, do not have appropriate skills or knowledge for good PE teaching and do not feel confident teaching PE. Similarly, Elliot, Atencio, Campbell and Jess (2013) noted among non-specialist primary school teachers in Scotland that their early school experiences of PE formed their beliefs of the subject, influenced their teaching confidence and affected their PE teaching practices. Teachers also commented that TE did not adequately prepare them, which was partially related to limited time in PEspecific training.…”
Section: Occupational Socialization Theory As Theoretical Frameworkmentioning
confidence: 99%